KONFLIK DAN RESOLUSI KONFLIK BERBASIS MODAL SOSIAL (STUDI KASUS KONFLIK PERKEBUNAN ANTARA PTPN V DENGAN MASYARAKAT KENEGERIAN DESA SENAMA NENEK KECAMATAN TAPUNG HULU KABUPATEN KAMPAR - Nuriadi, Nuriadi; Yulida, Roza; Kausar, Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Land conflicts often occur because of the promising potential of plantation resources and business opportunities. This study discusses the case study case of land conflicts of 2800 ha between the villagers of SenamaNenek and PTPN V SeiKencana gardens. The objectives of this research are: 1) identify conflict-causing factors; 2) analyze conflict resolution strategies; 3) analyze social capital conditions; 4) formulate social capital based conflict resolution strategies. This research use method: survey method, puposive sampling technique and snowball sampling with number of respondents 20 people. Data analysis using Likert scale for research purposes one to three. SWOT analysis for four research purposes. The main factor of the conflict was the inappropriate aspect of the award with a high score of 4.65. conflicting conflict resolution is negotiation 3.62 high category the most influential social capital after the conflict was the 2.00 aspect of the relationship with the low category. social capital based resolution strategy: 1) The company needs to provide compensation in accordance with the agreement, 2) Increase Solidarity to defend the ulayat land of the kenegerian community Senen Grandma village, 3) With good community bonds will unite existing perceptions and make agreement in the settlement of conflict. Keywords : Conflict, Conflict Resolution, and Social Capital